Application of Pasal 98 Ayat (2) and (3) Jo Pasal 196 Undang-Undang No 36 of 2009 Concerning Health (Analysis of Decision No. 134/Pid.Sus/2023/Pn. Skb) - Kordelina S, Eneng Raima; Juhana, Ujuh (Journal of Law, Politic and Humanities, 2024)
This study aims to analyze the application of Pasal 98 ayat (2) and (3) jo Pasal 196 Undang-Undang No. 36 of 2009 concerning Health based on Decision No. 134/Pid.Sus/2023/PN. Skb. The phenomenon of the problem raised is the rise of criminal acts in the health sector, especially the circulation of pharmaceutical preparations without a distribution permit, which can endanger public health. This research uses a normative juridical method with a literature study approach and field studies, as well as the opinions of experts related to applicable UUs and regulations. The data collection techniques used are literature study and field study with a statutory approach and case approach. The results showed that the application of Pasal 98 ayat (2) and (3) in the case of the crime of distribution of pharmaceutical preparations without a distribution permit had been carried out appropriately. The defendant Fajar Kholif alias Babang bin Deden Surahman was sentenced to imprisonment for 1 year and 10 months and a fine of Rp. 5,000,000, with evidence in the form of 340 items of Tramadol HCI type drugs which were destroyed. The judge considered relevant and valid evidence, as well as aggravating and mitigating factors in handing down the verdict.